Biodeterioration Due to Improper Exploitation of External Facades = Biodeterioracja wywołana niewłaściwą eksploatacją elewacji zewnętrznych - Piontek, Marlena; Lechów, Hanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Unaesthetic stains and deposits often form on external facades (especially those facing the north) in places where barriers were installed on them. Such places include, for example: fragments of facades in which external window sills were mounted, canopies, downspouts, boxes, advertising billboards, flags holders, lightning conductors, aerials as well as facade steps, and many others.
Keywords: facades; buildings; facade exploitation; biodeterioration; deposits; stains; elewacje; budynki; eksploatacja elewacji; biodeterioracja; nalot; zaciek